Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 1 - Functions and Limits - Review - Exercises - Page 97: 29



Work Step by Step

$\lim\limits_{h \to 0}\dfrac{(h-1)^3+1}{h}$ Expand: $\lim\limits_{h \to 0}\dfrac{h^3-3h^2+3h-1+1}{h}$ $\lim\limits_{h \to 0}\dfrac{h^3-3h^2+3h}{h}$ $\lim\limits_{h \to 0}h^2-3h+3$ Plug in 0: $0^2-3(0)+3=3$ $\lim\limits_{h \to 0}\dfrac{(h-1)^3+1}{h}=3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.